Interaction of toxic chemicals with microplastics: A critical review - Wang, Fen; Wong, Charles S.; Chen, Da; Lu, Xingwen; Wang, Fei; Zeng, Eddy Y. (Water research (Oxford), 2018)
Occurrence of microplastics (MPs) in the environment has attracted great attention as it has become a global concern. This review aims to systematically demonstrate the role of marine microplastic as a novel medium for environmental partitioning of chemicals in the ocean, which can cause toxic effects in the ecological environment. This review assimilated and analyzed available data published between 1972 and 2017 on the interaction between MPs and selected chemicals. Firstly, the review analyzes the occurrence of chemicals in MPs and outlines their distribution patterns. Then possible mechanisms of the interaction between MPs and organic chemicals and potential controlling factors were critically studied. Finally, the hazards of MPs and affiliated organic chemicals to marine organisms were shortly summarized. [Display omitted] •The toxic chemicals found in microplastics were outlined with detailed analysis.•The interaction mechanisms between chemicals and microplastics were analyzed.•The potential effects of microplastics on marine organisms were summarized.